Exploring the Potential as Molecular Quantum-Dot Cellular Automata of a Mixed-Valence ru2 Complex Deposited on a Au(111) Surface - Montenegro-Pohlhammer, N (Royal Society of Chemistry, 2023)
A key requirement for the implementation of molecular quantum dot cellular automata (mQCA) is the ordered attachment of molecules on surfaces. In this work we explore by means of state-of-the art quantum chemistry calculations different aspects of the deposition of a mixed-valence Ru2+ complex on Au(111), underlined as a promising component in mQCA. Our results provide information about the geometry adopted by the Ru2+ molecule and the counterion PF6− on the metal surface and the electronic structure of the doublet ground state, with the excess charge localized on one side of the molecule, not only on the Ru centre, but also involving a part of the 12-carbon bridging chain, which could explain the pair of bright/dim features of STM images. Our calculations also test the functionality as the mQCA of the Ru2+ molecule, evaluating the response curve under an applied electric field as perturbation, and the electronic distribution of two neighbouring Ru2+ molecules forming a four-dot cell, with a diagonal organization of the two excess charges. To the best of our knowledge, this is the first study devoted to the analysis of the electronic structure and mQCA functionality of deposited mixed-valence molecules. © 2023 The Royal Society of Chemistry.